2018
DOI: 10.1128/aac.00758-18
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in epaR Confer Resistance to ϕNPV1 Infection in Enterococcus faecalis OG1RF

Abstract: Enterococcus faecalis is a Gram-positive opportunistic pathogen that inhabits the human gastrointestinal tract. Because of the high frequency of antibiotic resistance among Enterococcus clinical isolates, interest in using phage to treat enterococcal infections and to decolonize high-risk patients for antibiotic-resistant Enterococcus is rising.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 42 publications
8
61
1
Order By: Relevance
“…3 and Table S1). This is consistent with a recent study demonstrating that mutation of epaR in E. faecalis OG1RF results in resistance to infection by the phage NPV1 (16). The remaining mutations in the phage-resistant isolates mapped to variable-region epa genes, including epaS, epaW, epaX, and epaAC ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…3 and Table S1). This is consistent with a recent study demonstrating that mutation of epaR in E. faecalis OG1RF results in resistance to infection by the phage NPV1 (16). The remaining mutations in the phage-resistant isolates mapped to variable-region epa genes, including epaS, epaW, epaX, and epaAC ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have demonstrated that core epa genes are important for phage infection of E. faecalis (16)(17)(18). To confirm the role of epa variable genes in facilitating phage infection of the NMRC phages, we generated in-frame deletion mutants of epaS and epaAC in E. faecalis V583 using allelic replacement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tn-Seq identified numerous E. faecalis genes that govern VPE25 susceptibility. Mutations in epa variable genes conferred VPE25 resistance by preventing phage adsorption, similar to other E. faecalis phages (23,(35)(36)(37). We discovered that phage infection of mismatch repair gene mutants results in the emergence of phage adsorption deficiencies; thus, the mismatch repair system likely fails to correct DNA damage of epa genes during phage infection.…”
Section: Discussionmentioning
confidence: 78%
“…The epa genes encode proteins involved in the formation of a cell surface-associated rhamnose-containing polysaccharide (34). We and others have previously demonstrated that enterococcal phages unrelated to VPE25 utilize Epa to adsorb and infect E. faecalis (23,(35)(36)(37). Initial work from our group showed that mutation of the VPE25 receptor Pip EF prevented VPE25 DNA entry into E. faecalis V583; yet, phages could still adsorb to receptor mutants (32), suggesting that the factors that promote phage infection via surface adsorption remained to be identified.…”
mentioning
confidence: 99%